2023
DOI: 10.1262/jrd.2022-122
|View full text |Cite
|
Sign up to set email alerts
|

A more accurate analysis of maternal effect genes by siRNA electroporation into mouse oocytes

Abstract: Maternal RNA and proteins accumulate in mouse oocytes and regulate initial developmental stages. Sperm DNA combines with protamine, which is exchanged after fertilization with maternal histones, including H3.3; however, the effect of H3.3 on development post-fertilization remains unclear.Herein, we established an electroporation method to introduce H3.3 siRNA into germinal vesicle (GV)stage oocytes without removing cumulus cells. Oocyte-attached cumulus cells need to be removed during the traditional microinje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…As a result, we found that a relatively higher impedance value of 590 Ω allows for the lowest invasiveness and effective introduction of mRNAs into the GV oocytes enclosed with multiple layers of cumulus cells than the standard impedance value in the TAKE method and found that the MII oocyte is not suitable for EP with these settings. Yamamoto et al recently reported a successful suppression of the H3f3a/b gene expression by introducing siRNA (-23 bp) into mouse GV oocytes using electroporation in a manner similar to our study (Yamamoto et al, 2023). In this study, we introduced a much longer size of mRNAs of approximately 1.2 kbp and succeeded in the efficient expression of fluorescent proteins in the oocytes and embryos.…”
Section: Discussionsupporting
confidence: 76%
“…As a result, we found that a relatively higher impedance value of 590 Ω allows for the lowest invasiveness and effective introduction of mRNAs into the GV oocytes enclosed with multiple layers of cumulus cells than the standard impedance value in the TAKE method and found that the MII oocyte is not suitable for EP with these settings. Yamamoto et al recently reported a successful suppression of the H3f3a/b gene expression by introducing siRNA (-23 bp) into mouse GV oocytes using electroporation in a manner similar to our study (Yamamoto et al, 2023). In this study, we introduced a much longer size of mRNAs of approximately 1.2 kbp and succeeded in the efficient expression of fluorescent proteins in the oocytes and embryos.…”
Section: Discussionsupporting
confidence: 76%